The reflecting orietsntalis about dobut sourse on islam - Omer Hama Rasheed Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research focus view point, orietsntalis on the quran and sunna of muhamad (peace be up to him), this research consists of three part and prologue. The nature of the research required to have an introduction and three sections. The introduction includes thr importan of this matter and reason why we choose it. The first section includes the all doubts the holy quran and introdus the word, the second section includes the doubts on the quran in macca and madina, and biography of goldziher. The third section about the biography of muhamad (peace be up to him) and prophets sunnah. The section includes all doubts about holy Quran, and doubts on Quran in mecca and madina, the historys which that mentioned in Quran, and how to read Quran, the section about his doubt anout Prophets order (P.B.U.H), and Prophets sunnah. In conclusion could not do the real research for Islam, just he takes into eathly side, far away from the supernatural side.